Auditory abilities stimulation in preschoolers - Tamires Andrade Sakai; Laura Mochiatti Guijo; Dayane Aparecida Nascimento Barbosa; Camila Ribas Delecrode; Ana Cláudia Vieira Cardoso (Revista CEFAC, 2020)
ABSTRACT Purpose: 1) to verify the intervention effects of an informal auditory training program to stimulate auditory abilities for sound localization and sequential memory for verbal and non-verbal sounds, at school environment in a group of preschoolers; 2) to investigate the influence of the gender and age variables on the result of the Simplified Auditory Processing Test (test and retest). Methods: a prospective, analytical and intervention study developed at a Municipal School of Early Childhood Education. Fifty-one preschool children of both genders, aged between 4 and 6 years, participated in this study. To evaluate the intervention effects of the informal auditory training program, pre-and post-intervention procedures were performed, that is: meatoscopy, tympanometry and Simplified Auditory Processing Test. Appropriate statistical tests were applied, by adopting the 5% (0.05) significance level. Results: the comparison of the preschoolers’ performance on the test and retest showed a significant improvement in all auditory abilities assessed. Preschoolers showed a better performance in sound localization ability and a worse performance for sequential memory of nonverbal sounds ability, for both test and retest. Conclusion: in this population, the informal auditory training program showed to be effective and the age variable influenced the result of the Simplified Auditory Processing Test.